2019
DOI: 10.1016/j.psychres.2018.12.174
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and psychological follow-up of undergraduate and postgraduate medical students: Prevalence and associated factors. Results from the national BOURBON study

Abstract: Background. Physicians are at risk of burnout, anxiety and depression. Prevention is needed from the beginning of the medical studies to detect early poor mental health outcomes. Objective. To determine the prevalence and associated of psychiatric or psychological follow-up in a national sample of undergraduate and postgraduate medical students (UPMS). Methods. UPMS of the 35 French Medicine faculties were recruited through mailing lists and social networks between December 2016 and May 2017 and fulfilled Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 33 publications
3
28
0
4
Order By: Relevance
“…The majority are extremely motivated (Nuffer et al, 2017;Khalil et al, 2018), and believe that they need a college education to achieve their career goals (Ottenberg et al, 2016;Worly et al, 2018). These individuals consider all aspects of life from a global perspective (Fryer et al, 2016;Berger et al, 2019), tend to adopt technology at its highest levels (Hennessy et al, 2016;Shatto and Erwin, 2017), expect on-demand services (Orsini et al, 2016b) that are always available (Woolley and Fishbach, 2018;Manspeaker et al, 2019) and easily accessible (Fond et al, 2018;Lysak et al, 2018). Hence, they prefer educational opportunities that allow them to stay connected with technology (Agius et al, 2018), and expect their educators to do the same (Joshi et al, 2017;Mor et al, 2018).…”
Section: Generational Characteristics Of Present-day Health Care Profmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority are extremely motivated (Nuffer et al, 2017;Khalil et al, 2018), and believe that they need a college education to achieve their career goals (Ottenberg et al, 2016;Worly et al, 2018). These individuals consider all aspects of life from a global perspective (Fryer et al, 2016;Berger et al, 2019), tend to adopt technology at its highest levels (Hennessy et al, 2016;Shatto and Erwin, 2017), expect on-demand services (Orsini et al, 2016b) that are always available (Woolley and Fishbach, 2018;Manspeaker et al, 2019) and easily accessible (Fond et al, 2018;Lysak et al, 2018). Hence, they prefer educational opportunities that allow them to stay connected with technology (Agius et al, 2018), and expect their educators to do the same (Joshi et al, 2017;Mor et al, 2018).…”
Section: Generational Characteristics Of Present-day Health Care Profmentioning
confidence: 99%
“…This often leads to professional burnout, a multifactorial syndrome, characterized by high levels of emotional exhaustion, depersonalization, and a reduced sense of personal accomplishment (Walker et al, 2016;Chen et al, 2017;Pape et al, 2018). Studies have reported that even having one burnout symptom can cause negative effects that not only interfere with learning (Mohr et al, 2011;Lopes et al, 2015;Lowe et al, 2016), but can also cause physical (Mahoney et al, 2016) and psychological symptoms (de Paiva et al, 2017;Fond et al, 2018), and even the use of illicit drugs (Brown et al, 2016;Merrill and Carey, 2016;Chen et al, 2017). Recent studies have reported that the development of burnout in health care students can be directly related to low levels of IM in these students (Rosenman et al, 2014;Lowe et al, 2016;Fond et al, 2018;Worly et al, 2018).…”
Section: Challenges Of Present-day Health Care Educationmentioning
confidence: 99%
See 3 more Smart Citations